The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2014
DOI: 10.1111/evo.12546
|View full text |Cite
|
Sign up to set email alerts
|

A highly pleiotropic amino acid polymorphism in theDrosophilainsulin receptor contributes to life-history adaptation

Abstract: Finding the specific nucleotides that underlie adaptive variation is a major goal in evolutionary biology, but polygenic traits pose a challenge because the complex genotype–phenotype relationship can obscure the effects of individual alleles. However, natural selection working in large wild populations can shift allele frequencies and indicate functional regions of the genome. Previously, we showed that the two most common alleles of a complex amino acid insertion–deletion polymorphism in the Drosophila insul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
139
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(152 citation statements)
references
References 76 publications
10
139
3
Order By: Relevance
“…Paaby & Schmidt, ): genotypes that confer stress resistance and survival at the expense of reduced fecundity might be favoured at high latitudes, where seasonal stressors such as cold and food shortage impose strong selection on somatic maintenance, whereas at low latitude, selection might favour alternative genotypes that confer fast development and high fecundity at the expense of reduced stress resistance and survival. In support of this adaptive scenario, we observed that high‐latitude flies from Maine lived longer and were more resistant to starvation and cold stress than low‐latitude flies from Florida, consistent with previous observations along the North American cline (Schmidt et al., , , b; Schmidt & Paaby, ; Paaby et al., ; Mathur & Schmidt, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Paaby & Schmidt, ): genotypes that confer stress resistance and survival at the expense of reduced fecundity might be favoured at high latitudes, where seasonal stressors such as cold and food shortage impose strong selection on somatic maintenance, whereas at low latitude, selection might favour alternative genotypes that confer fast development and high fecundity at the expense of reduced stress resistance and survival. In support of this adaptive scenario, we observed that high‐latitude flies from Maine lived longer and were more resistant to starvation and cold stress than low‐latitude flies from Florida, consistent with previous observations along the North American cline (Schmidt et al., , , b; Schmidt & Paaby, ; Paaby et al., ; Mathur & Schmidt, ).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests a pattern of climatic adaptation whereby harsh winters and seasonal stress at high latitudes favour stress resistance and overwintering ability (dormancy), along with correlated (e.g. pleiotropic) responses in terms of larger body size, increased lifespan and reduced fecundity (Schmidt & Paaby, ; Paaby & Schmidt, ; Flatt et al., ; Paaby et al., ). Yet, whether clinal inversion polymorphisms such as In(3R)P contribute to this pattern of phenotypic climatic adaptation is largely unclear (De Jong & Bochdanovits, ; Hoffmann et al., ; Rako et al., ; Hoffmann & Weeks, ; Hoffmann & Rieseberg, ; Kapun et al., , b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…If we treat cpo as the true seasonal locus, this result implies that we lack power to discover many many causal genes involved in seasonal adaptation. There was no excess of seasonal SNPs surrounding the insulin receptor (InR), wherein seasonally variable indels and SNPs had been previously reported (Paaby et al 2014).…”
Section: Cc-by-nc-ndmentioning
confidence: 95%
“…Studies in flies and beetles have likewise suggested the IIS as a major pathway involved in resource distribution. An exonic indel polymorphism in the insulin-like receptor (lnR) gene was identified as a functional direct candidate target of natural selection in wild D. melanogaster [72,73]. In rhinoceros beetles, horn size is highly sensitive to nutrition and to perturbations in the IIS than are other body structures [74].…”
Section: (I) Large Effect Mutations Support the Idea That Major Signamentioning
confidence: 99%